Using Reflective Journals to Compare an International Faculty-led Study Tour and Student Internship Experience - Amanda N. Northfell; Leslie D. Edgar (Journal of Applied Communications, 2014)
The globalization of society presents the need for intercultural communications skills. International experiences impact students’ global perceptions, which affect the agricultural industry’s future. This study sought to determine agricultural students’ values and how these values influenced their perceptions regarding their unique international experiences. Students from four universities who participated in a three-week faculty led study tour (N = 11) were compared to University of Arkansas students who participated in a six-week internship (N = 5) in Ghent, Belgium. Students used reflective journals to record their perceptions, and a content analysis was conducted to identify emergent themes. Students from both experiences struggled most when communicating with researchers, but they gained confidence as they successfully served an international client. Host families were the most pressing concern for students, but those family stays were impactful in exposing students to Belgian culture. Students sought normalcy by comparing Europe to America and stepped up as leaders when faculty guides were not present. Regardless of whether students were led by a faculty member (study tour) or navigated the international experience predominately on their own (internship), each found value in studying internationally. Previous research recommended placing students in international settings to increase students’ knowledge of global agriculture, and this concept is reinforced by this study.
Keywords: Reflective journals; international internships and study tours; agricultural communications.